PENGARUH MINDFULNES TERHADAP PENURUNAN KECEMASAN BIDAN DALAM KASUS KEGAWATDARURATAN DI KLINIK ASTER TAHUN 2024 - Damar Aulia Nissa; Rina Dwi Anggraeni; Dewi Rubi Fitriani (Journal of Innovation Research and Knowledge, 2024)
Anxiety is a person's emotional response that is not clear and can cause feelings of discomfort and threat. Although it is characterized by constant worry and anxiety, it is actually not anxiety that comes from outside the body. The purpose of this study is to test the effect of mindfulness therapy on midwifery anxiety. The research method used is pre-test, post-test single group design with the selection of non-probability samples, namely purposive samples of 15 midwives working at the 2024 Aster Clinic using a quasi-experimental design. The results of this study show that there is a significant influence between the use of mindfulness therapy in reducing midwifery anxiety. This result is strengthened by the results of an analytical test using the Wilcoxon test. The pre-test and post-test showed a significant difference in anxiety levels between the two with a p-value of 0.008 meaning that mindfulness therapy could make a big difference in reducing midwifery anxiety. The concept of mindfulness therapy can help reduce midwifery anxiety